"I Can Do It in No Time!" Time Predictions in the Cultural Context. - Guan, Li; Wang, Qi (Journal of Cross-Cultural Psychology, 2026)
Two studies were conducted to examine predictions of task completion times and the factors that influence time planning in the cultural context. European-American and Asian adults (Study 1) and European-American, Asian-American, Chinese college students (Study 2) were asked to predict task completion times in hypothetical scenarios. Participants were randomly assigned to a lesson-learning condition where they were reminded of relevant past experiences, a social consequence condition where they were warned of potential negative social consequences of planning failure, or a control condition. Study 1 revealed that Asians, but not European Americans, predicted longer task completion times in the two experimental conditions than controls. Study 2 showed that although European Americans, Asian Americans, and Chinese all provided longer predicted times in the two experimental conditions than controls, Chinese made the most pronounced increase in their time predictions. These original findings have important implications for the planning fallacy and its intervention.